The conversion of null legal business in the main legal systems of Europe and Latin America. (theoretical-normative scope of this remedy in extremis) - Cortez Pérez, César Daniel (2020)
In this article, a presentation will be made of the legal institution of the conversion of the null legal business in the different European and Latin American legal systems, such as the civil legal systems of Germany, France and Italy for Europe and the civil legal systems of Argentina, Chile and Brazil for Latin America, the presentation of this institute in these systems will be theoretical-normative. The conversion of the null legal business is an institution that is not regulated in Peru, however, in other countries it has a wide doctrinal development, being regulated in different civil codes that we can classify as cutting edge. What is proposed in this article once this institution has been presented in different foreign realities, is the regulation of the conversion into the Peruvian civil code, based on the existence of yesterday's guidelines and intentions that today would protect this proposal.